Mineral content of different bottled water available in Bangladesh: Assessment of their compliance with current regulations - Rahman, Mohammad Arifur; Salam, Md Abdus; Salam, Abdus; Roy, Madhusudan; Ara, Nargis Jahan; Alam, AM Shafiqul (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Nine bottled water brands collected from retail shops and food shops beside the University of Dhaka were analyzed for their major and trace element constituents to ascertain their suitability for human consumption. The results obtained were compared with parametric values (PVs) set by European Community Council Directive 98/83/EC and the guideline values (GVs) recommended by WHO. It was found that the majority of the brands tested were low in mineral contents. Moreover, lower values of hardness, TDS and conductivity than the prescribed limits of WHO showed that water was deficient in essential minerals. Minerals like magnesium, potassium, calcium were present in some cases in such a low concentration that water seemed to be as good as distilled water. In case of heavy metals, only lead and cadmium were found to be below the detection limit (0.001 mg/L) which indicates bottled water brands are better for drinking. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15316 J. Asiat. Soc. Bangladesh, Sci. 38(1): 7-15, June 2012